2001
DOI: 10.1152/jn.2001.85.4.1444
|View full text |Cite
|
Sign up to set email alerts
|

Model for Olfactory Discrimination and Learning inLimaxProcerebrum Incorporating Oscillatory Dynamics and Wave Propagation

Abstract: We extend our model of the procerebral (PC) lobe of Limax, which is comprised of a layer of coupled oscillators and a layer of memory neurons, each layer 4 rows by 20 columns, corresponding to the cell body layer (burster cells) and neuropil layer (nonburster cells) of the PC lobe. A gradient of connections in the layer of model burster cells induces periodic wave propagation, as measured in the PC lobe. We study odor representations in the biological PC lobe using the technique of Kimura and coworkers. Lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 72 publications
1
28
0
1
Order By: Relevance
“…Tables 1 and 2 show the details of LY-labeled neurons. As reported by Kimura et al (1998b) and Ermentrout et al (2001), a cluster of LY-labeled neurons was observed in one side of the PC lobe. Several LY-labeled neurons were observed in the PC lobe contralateral to the PC lobe classified as "labeled" and in the PC lobes classified as "unlabeled," though in these cases the LY-labeled neurons did not form a cluster (Table 1).…”
Section: Ly Uptakesupporting
confidence: 82%
See 2 more Smart Citations
“…Tables 1 and 2 show the details of LY-labeled neurons. As reported by Kimura et al (1998b) and Ermentrout et al (2001), a cluster of LY-labeled neurons was observed in one side of the PC lobe. Several LY-labeled neurons were observed in the PC lobe contralateral to the PC lobe classified as "labeled" and in the PC lobes classified as "unlabeled," though in these cases the LY-labeled neurons did not form a cluster (Table 1).…”
Section: Ly Uptakesupporting
confidence: 82%
“…The application of learned odors changes the frequency of the LFP oscillation (Kimura et al 1998a;Inoue et al 2006). In addition, when a fluorescent dye, Lucifer Yellow (LY), is injected into the body cavity after odor learning, some of the PC interneurons incorporate the dye (Kimura et al 1998b;Gelperin 1999;Ermentrout et al 2001). Since the incorporation of LY depends on conditioning treatment and the duration between conditioning and LY injection (Kimura et al 1998b), LY-labeled neurons are related to the formation of memory of learned odors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been made to understand odor discrimination in models of the olfactory system [17,51,13,26,9,3,32,19]. The model discussed here is, however, fundamentally different in providing a classification scheme that solely relies on the fan-in, fan-out properties of synaptic connections, the known locus of learning in the MB and otherwise entirely non-specific connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the PC exhibits a learned odor-specific change in the oscillatory frequency or amplitude of the spontaneous local field potential oscillation (Kimura et al, 1998a;Nikitin and Balaban, 2000;Inoue et al, 2006), and incorporation of Lucifer yellow dye into PC neurons specifically following odor-associative memory formation (Kimura et al, 1998b;Ermentrout et al, 2001;Sekiguchi et al, 2010). Future studies may reveal such discernible changes triggered in the TG by olfactory learning.…”
Section: Discussionmentioning
confidence: 99%